Inverted Classroom: an experimental analysis in times of pandemic (LACCEI, 2024)
The implementation of the Flipped Classroom model in times of pandemic was a complete success, however, the previous implementation allowed for experience, both in teachers and students. It is necessary to mark the three moments of this model to understand that each stage is important. The before, during and after are decisive to consolidate learning. The objective of this study is to analyze the previous part (before) of the implementation of the Flipped Classroom model in the mathematics subjects that are taught in the first year of studies in the various careers. At the same time, a systematic review of the literature and the contextualization of mathematics difficulties were carried out. As a result, an improvement in the academic performance of the classrooms was observed, where a new way of working was developed, in which a video was added that included questionnaires that were necessary to complete in order to advance in the class Also, an improvement in grades. Finally, the research proposes the implementation of the flipped classroom, since motivating benefits are observed, such as student satisfaction.